Measuring the Impact of the Interrelationship between the Population Growth Index and the Human Development Index (HDI) in Iraq during the Period (2004-2024) - Mustafa Nawfal Wajeeh (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The interplay between demographic trends and socioeconomic welfare constitutes a central focus within macroeconomic literature. Specific Background In Iraq, an economy dependent on oil revenues, the population expanded significantly from 2004 to 2024 alongside gradual improvements in public welfare indicators. Knowledge Gap Despite recognized demographic shifts, the precise unidirectional or bidirectional causal linkages between population expansion and welfare improvements remain insufficiently quantified within this specific regional context. Aims This study investigates the exact causal direction between the population growth index and the Human Development Index (HDI) in Iraq during the 2004–2024 period. Results Utilizing the Toda-Yamamoto causality test and a vector auto-regression model, the analysis reveals no statistically significant causation flowing from demographic expansion to welfare improvement; conversely, a significant causal transfer exists flowing directly from HDI advancements to population growth. Novelty This research distinctly isolates a unidirectional demographic dependency on welfare metrics in a transitioning economy, refuting assumptions of mutual causality through advanced lag-selection econometric testing. Implications Policymakers must diversify national income sources beyond oil and prioritize sustainable infrastructure, education, and healthcare investments to accommodate the demographically expansive consequences of rising living standards. Highlights: Toda-Yamamoto causality tests confirm unidirectional causation transferring directly toward demographic growth. Econometric testing reveals no significant reciprocal correlation flowing backward toward societal prosperity. Diversifying national revenue streams is necessary to support essential infrastructure and health sectors. Keywords: Human Development Index, Iraqi Population Metrics, Toda-Yamamoto Causality, Demographic Expansion, Sustainable Public Infrastructure